A Study Of Farm-Level Input Demands Without Seed Selectivity Adjustment on Rice Farms in The Cimanuk River Basin, Jawa Barat - Budiman Hutabarat (Jurnal Agro Ekonomi, 1986)
This paper is an attempt to analyze how a rice farmer responds to economic stimulus through allocating his resources reflected in elasticities of input demands. Specifically, in the model seed selectivity adjustment is not taken into account, that is, modern and traditional variety farmer elasticities are separately computed and then compared. The sample farmers were drawn from six desas in the area of the Cimanuk River Basin, Jawa Barat, which has been and still is currently dominated by rice farming. The results show that the own-price elasticities of demand for nitrogen fertilizer of TV (traditional variety) farmers are higher than that of MV (modern variety) farmers. These elasticities tend to decline overtime.